5 - Reconnecting the University to Society: The Role of Knowledge as Public Good in South African Higher Education - Ndofirepi, Amasa; Cross, Michael (Journal of Higher Education in Africa, 2022)
This article discusses the nature of university–society relations in response to the calls on South African universities for greater social and economic responsiveness driven by external stakeholders. The adoption of constitu- tional democracy and the provision of institutional autonomy have provided them with considerable freedom to pursue their goals in society. However, they have also left them under considerable pressure from competing inter- est groups, intensifying the levels of internal and external determination, very often in a conflicting manner. The article argues that current forms of determination (e.g. Constitutional framework, policy and stakeholder demands) on university operations cannot per se provide adequate options for university–society relations. Critical to effective university–society relations is the structure of production and distribution of knowledge. The problem in this regard stems from the failure to recognize the encroach- ment of the profit motive into the academy (the shift from a public good knowledge/learning regime to a neoliberal knowledge/learning regime). Under such circumstances, progressive virtues (self-development, positive human relations and informed citizenship), democratic principles (equity and social justice) and the commitment to social transformation guided by altruism and common good encapsulated in the South African higher education vision are under serious threat.